The effects of personality on perceived power and the integrativeness of negotiation agreements - Barbosa, Marta Amaral Martins Cabral de (2020)
Negotiation skills are of paramount importance, not only in business but in daily life, and even more so in an increasingly interconnected world. By understanding the psychological processes and the interpersonal dynamics governing negotiations, better outcomes can be achieved by all parties, whether greater economic benefits or healthier relationships or both. With recourse to a simulated negotiation game and a sample of volunteering postgraduates, this study explored the impact of an individual's personality on individual outcomes and perception of power, and also the interaction between different personality types within the negotiation dyad and its impact on joint gains. Extroverts were found to report higher perceived power, to have higher aspirational values and to achieve better distributive outcomes than introverts. Dyads composed of only extroverts were able to reach the most integrative agreements. Surprisingly, extroverts negotiating with introverts achieved the lowest average joint gains, denoting some incompatibilities in the interrelation between the two personality types.